THE COMPARTMENT MODEL WITH INTERVENTION FOR STUNTING PREVALENCE - Sari, Yulia Retno; Samat, N.A (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This study aims to propose a new mathematical model to reduce the prevalence of stunting with interventions given to children aged 0 months to less than 24 months. The interventions given are how often toddlers are checked for health at integrated health centers, breastfeeding, complementary feeding and immunization. This study develops a compartment model that considers the basic characteristics of stunting transmission and interventions that will be given to toddlers diagnosed with stunting. This mathematical model will include the development of difference equations and differential equations to represent the transmission of stunting prevalence in real life. This new initial mathematical model can be used by authorities as a prevention strategy to reduce the prevalence of stunting. The extension of this study will include the application of the proposed mathematical model to stunting data in Indonesia.